2014
DOI: 10.1021/jo502595g
|View full text |Cite
|
Sign up to set email alerts
|

Chloro, Difluoromethylation and Chloro, Carbomethoxydifluoromethylation: Reaction of Radicals Derived from RfSO2Cl with Unactivated Alkenes under Metal-Free Conditions

Abstract: Difluoromethyl and carbomethoxydifluoromethyl radicals were generated from their respective sulfonyl chlorides under mild, metal-free conditions leading to efficient atom transfer radical additions (ATRA) to unactivated alkenes to form chloro, difluoromethylated and chloro, carbomethoxydifluoromethylated products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 52 publications
0
19
1
Order By: Relevance
“…An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)…”
mentioning
confidence: 91%
“…[6] Simultaneous incorporation of as econd functional group into molecules would allow further transformation;t he second functional group could also have excellent potential for the design of pharmaceuticals and agrochemicals.T herefore,m uch effort has been devoted to development of efficient methods for difluoromethylative difunctionalization of alkenes,i ncluding hydrodifluoromethylation, [7] carbodifluoromethylation, [8] oxydifluoromethylation, [9] and halodifluoromethylation. [10] Then itrile group (CN) is av ersatile functionality in synthetic chemistry and life sciences,a nd thus cyanation has received much attention. [11] Va rious cyanationr eagents have been developed, such as NaCN,K CN,a nd trimethylsilyl cyanide (TMSCN).…”
mentioning
confidence: 99%
“…[19] Also, not unexpectedly, simple thermally induced radical initiators, such as AIBN and dilauroyl peroxide (DLP) were also found to be ineffective in promoting the desired reaction (Table 1, entries 5 and 6), although we have recently found that similar reactions of fluoroalkylsulfonyl chlorides with electron-rich alkenes produced 1:1 adducts in high yields when using DLP as the radical initiator. [20] We were encouraged, however, to find that the use of Ir(ppy) 3 in place of the Ru catalysts led to a 43-44 % yield of addition product (Table 1, entries 7 and 8). This result probably indicated that Ir IV was a better mediative source of the Cl atom than was Ru III .…”
mentioning
confidence: 99%
“…Using the reaction of CF 3 SO 2 Cl with N ‐methyl‐ N ‐phenylacrylamide ( 2 a ) as model reaction for exploratory experiments, we did not find reaction conditions that produce a significant yield of addition product when using either Ru(phen) 3 Cl 2 or Ru(bpy) 3 Cl 2 as catalysts (Table 1, entries 1–4), in spite of the fact that these catalysts had been effective in the ATRA reaction of CF 3 SO 2 Cl with electron‐rich alkenes 19. Also, not unexpectedly, simple thermally induced radical initiators, such as AIBN and dilauroyl peroxide (DLP) were also found to be ineffective in promoting the desired reaction (Table 1, entries 5 and 6), although we have recently found that similar reactions of fluoroalkylsulfonyl chlorides with electron‐rich alkenes produced 1:1 adducts in high yields when using DLP as the radical initiator 20…”
Section: Methodsmentioning
confidence: 99%